Lags and Leads in Life Satisfaction : A Test of the Baseline Hypothesis - Yannis Georgellis; Ed Diener; Andrew E. Clark; Richard E. Lucas (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
We use fourteen waves of the German panel data to ask whether individuals, after life and labour market events, return to some baseline wellbeing level. Although the strongest life satisfaction effect is often at the time of the event, significant lag and lead effects are present. Men are more affected by labour market events (unemployment and layoffs) and women by life events (marriage and divorce). Anticipation is an important component of individual wellbeing. Last, we show that happiness does not provide insurance against hard knocks: those with high baseline satisfaction are most adversely affected by negative events.
Keywords: 330; Life Satisfaction; Anticipation; Habituation; Baseline Satisfaction; Labour Market and Family Events; Lebensqualität; Lebensverlauf; Erwerbsverlauf; Familiensoziologie; Deutschland